2019
DOI: 10.1063/1.5055053
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional modal and non-modal instabilities in straight-diverging-straight channel flow

Abstract: A systematic study of a two-dimensional viscous flow through the straight-diverging-straight (SDS) channel defined by two straight-walled sections of different widths and a divergent section in-between is presented here. It has the plane Poiseuille flow (PPF) and the symmetric sudden expansion flow as the limiting cases. The topology of steady laminar flows and its bifurcations are characterized in the multi-parametric space formed by the divergence angle, the expansion ratio, and the Reynolds number. Three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
6
11
0
Order By: Relevance
“…The deflection of the flow in channel sudden expansion geometries is well documented [33,34,35,36], however, to the authors knowledge, only the references mentioned above include the appearance of a non-symmetrical configuration on two-dimensional base bleed configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The deflection of the flow in channel sudden expansion geometries is well documented [33,34,35,36], however, to the authors knowledge, only the references mentioned above include the appearance of a non-symmetrical configuration on two-dimensional base bleed configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional axisymmetric Navier–Stokes simulations also reported the effect of the diverging angle and Re on the onset of the laminar recirculations (Peixinho and Besnard, 2013). In diverging channel flow, Jobkar et al (Jotkar and Govindarajan, 2019; Jotkar et al , 2015) further showed the effect of the angle and the expansion ratio. Small angles delay the onset of the critical Re and small expansion ratios also delay the critical Re .…”
Section: Introductionmentioning
confidence: 99%
“…The reverse transitions did not depend on the ratio of pipe diameter to length. Various studies have examined divergent pipe flow or sudden expansion pipe flow 12 14 , 17 20 . If those studies had examined flow condition farther downstream, the reverse transition would have been observed.…”
Section: Resultsmentioning
confidence: 99%